Progress for the poor - Kenworthy, Lane. (New York : Oxford University Press, 2011)
One of the principal goals of antipoverty efforts should be to improve the absolute living standards of the least well-off. This book aims to enhance our understanding of how to do that drawing on the experiences of twenty affluent countries since the 1970s.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: Poverty -- Government policy; Poor -- Government policy; Social policy; Economic development